Effect of inclusion of Azolla on performance, haematobiochemical parameters and economics in Japanese quail broilers - VERMA, KALYANI; PRUSTY, SONALI; GENDLEY, M K; DUBEY, MEENU; RAMTEKE, R C; DONERIA, RAINA (The Indian Journal of Animal Sciences, 2024)
An experiment was conducted to study the effect of dietary supplementation of Azolla on the performance of Japanese quail broilers. Day old Japanese quails (135) were divided into three treatment groups with three replicates per treatment and 15 quails in each replicate. The feeding of birds was done in two phases from 1-3 weeks and 4-5 weeks. Azolla was included at 0%, 5% and 10% levels in T0 (control), T1 and T2 groups, respectively. Azolla inclusion did not show any significant effect on the feed intake up to 5 weeks of age. Body weight gain and PCV%, total protein and albumin were significantly higher at 5% level whereas no significant difference was observed at 10% level of Azolla inclusion. Azolla at both 5% and 10% level significantly reduced serum cholesterol concentration and the highest net profit was in 10% Azolla supplemented group. So, Azolla can be included effectively at 10% level in diet of Japanese quail broiler.